Natural history of ovarian endometrioma in pregnancy - Pateman, Katie (BMC Womens Health, 2014)
BACKGROUND: Ovarian endometriomas are classified as benign ovarian lesions. During pregnancy endometriomas may undergo major morphological changes which are referred to as ‘decidualisation’. Decidualised ovarian endometrioma may resemble malignant ovarian tumours on ultrasound examination. The aim was to study variations in the morphology and size of ovarian endometriomas diagnosed on ultrasound during pregnancy. METHODS: We searched our database to identify pregnant women who were diagnosed with ovarian endometriomas on ultrasound in order to study the effect of pregnancy on their morphological characteristics. In women who underwent serial scans during pregnancy we examined the changes in the size of endometriomas with advancing gestation. RESULTS: Twenty four patients with a total of 34 endometriomas were included in the analysis. All women were managed expectantly during pregnancy. On the first ultrasound scan 29/34 (85.3%, 95% CI 73.4 - 97.2) endometriomas appeared unilocular with fine internal echoes (‘ground glass’ contents) and they were poorly vascularised on Doppler examination. 1/34 (2.9% 95% CI 0.0 - 8.5) endometrioma was multilocular, with regular margins, ‘ground glass’ contents and it was also poorly vascularised. 4/34 (11.8%, 95% CI 1.0 - 22.6) had sonographic features suggestive of decidualisation such as thick and irregular inner wall, papillary projections and highly vascular on Doppler examination. The endometriomas showed a tendency to decrease in size during pregnancy. CONCLUSIONS: Pregnancy has a major effect on the size and morphological appearances of ovarian endometriomas. Rapid regression of decidualised endometriomas is a helpful feature which could be used to confirm their benign nature.